2018
DOI: 10.1101/324327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-aging food that improves markers of health in senior dogs by modulating gut microbiota and metabolite profiles

Abstract: 19Dysbiosis is one of the major changes in aging that leads to an accumulation of toxic microbial 20 metabolites. The aim of this study was to evaluate the effect of a test food containing components of 21 citrus, carrot, spinach and tomato on gut microbiota and age-related metabolites in senior dogs. The 22 study was conducted on 36 dogs between 8 and 13 years of age. All dogs were maintained on a control 23 food (control 1), which used corn as major source of fiber. After 30 days, the dogs were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…In correlation with our results, in a human study, psyllium supplementation increased the fecal acetate concentration along with the amount of both succinate-specific utilizer Phascolarctobacterium and acetate metabolizing Faecalibacterium species [ 15 ]. Furthermore, according to other studies, increased fiber content of feed resulted in intensely elevated acetogenic bacterial content such as Ruminococcus , Phascolarctobacteria , Christensenellaceae and Ruminococcacea species in dogs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In correlation with our results, in a human study, psyllium supplementation increased the fecal acetate concentration along with the amount of both succinate-specific utilizer Phascolarctobacterium and acetate metabolizing Faecalibacterium species [ 15 ]. Furthermore, according to other studies, increased fiber content of feed resulted in intensely elevated acetogenic bacterial content such as Ruminococcus , Phascolarctobacteria , Christensenellaceae and Ruminococcacea species in dogs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, it can be also concluded that only psyllium was able to increase the concentration of n-butyrate, which can be in correlation with the shift in the canine intestinal microbiota towards Faecalibacterium, Christensenellaceae, Oscillospira and Ruminococcus spp. as the effect of fiber-rich diet, described in previous studies, since these bacteria are able to effectively convert sugars, acetate and other substrates into n-butyrate [ 15 , 47 ]. On the other hand, according to recent studies, the composition of the intestinal microbiota of healthy humans was less altered by psyllium administration than that of constipated people [ 15 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Encontram-se na literatura estudos que avaliaram o efeito de diversas dietas sobre a metabolômica, tanto em humanos (BEERMANN et al, 2003;BALDERAS et., 2010;WONG et al, 2012;PEREZ-CORNAGO et al, 2014) como em ratos (DINIZ et al, 2004;WANG et al, 2006), peixes (LIU et al, 2019), gatos (DENG et al, 2014), cães adultos (SCHMIDT et al, 2018) e cães idosos (GEBRESELASSIE et al, 2018).…”
Section: ôMega-3 E Metabolômicaunclassified